2022
DOI: 10.17485/ijst/v15i47.1633
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis, Antimicrobial and Antioxidant Activity of Mangrove Plants Bruguiera gymnorrhiza (L.) Lam. and Excoecaria agallocha L.

Abstract: Objectives: To perform a detailed phytochemical analysis, antimicrobial and antioxidant activity of leaf extracts of mangroves Bruguiera gymnorrhiza and Excoecaria agallocha. Methods: A comparative phytochemical analysis was done using qualitative and quantitative methods followed by antimicrobial activity and antioxidant analysis using DPPH. Aqueous and chloroform extracts of both mangroves were subjected to UV-Visible spectrum analysis. Further, the extracts were subjected to TLC, FTIR and GC-MS analysis to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Another study on Bruguiera gymnorrhiza found 67.2% aqueous extract followed by 67% methanol extract, whereas in the case of Excoecaria agallocha, 64.9% were in ethanol and 46.2% were in chloroform extract. 43 The crude methanol extract of selected mangroves has free radical scavenging. 44…”
Section: Extract Characteristics Of Mangrove Leavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study on Bruguiera gymnorrhiza found 67.2% aqueous extract followed by 67% methanol extract, whereas in the case of Excoecaria agallocha, 64.9% were in ethanol and 46.2% were in chloroform extract. 43 The crude methanol extract of selected mangroves has free radical scavenging. 44…”
Section: Extract Characteristics Of Mangrove Leavesmentioning
confidence: 99%
“…The total phenol content of the three mangrove species with the highest yield was 13.822 mg GAE/g in B. gymnorrhiza (Table 6). Many biological activities were known, such as phenols and flavonoids in B. gymnorrhiza leaves extract 43 . Furthermore, in S. alba, it was 9.4969 mg GAE/g.…”
Section: Dpph Radical Scavenging Activity Of Mangrove Leavesmentioning
confidence: 99%